2021
DOI: 10.1002/ange.202101390
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the Mechanistic Scenario of Carbon−Sulfur Nucleophilic Coupling via High‐Valent Cp*CoIV Species

Abstract: The potential access to Co IV species for promoting transformations that are particularly challenging at Co III still remains underexploited in the context of Cp*Co-catalyzed CÀ H functionalization reactions. Herein, we disclose a combined experimental and computational strategy for uncovering the participation of Cp*Co IV species in a Cp*Co-mediated C À S bond-reductive elimination. These studies support the intermediacy of high-valent Cp*Co species in CÀH functionalization reactions, under oxidative conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…159 A detailed mechanistic study by Maseras, Pérez-Temprano, and co-workers revealed the involvement of a Cp*Co(IV) species in the reductive elimination step of this transformation. 160 An oxidant-free thiolation of indoles using N -(arylthio)succinimides was reported by the Anbarasan group. 161…”
Section: C–h Activationmentioning
confidence: 99%
“…159 A detailed mechanistic study by Maseras, Pérez-Temprano, and co-workers revealed the involvement of a Cp*Co(IV) species in the reductive elimination step of this transformation. 160 An oxidant-free thiolation of indoles using N -(arylthio)succinimides was reported by the Anbarasan group. 161…”
Section: C–h Activationmentioning
confidence: 99%
“…Indeed, two recent studies 9 have outlined the central role of highly reactive transient Co(IV) metallacycles in C–H bond functionalization (Scheme 1 ), revealing that the nature of the X ligand, often introduced to functionalize the aromatic C–H bond, 10 is crucial. 9b Such Co(IV)–reactant complexes might indeed evolve by at least two main pathways: (1) the reductive elimination 9a (RE) desired in catalysis 10 or (2) the undesired collapse 9b of the key Cp*Co motif by a cyclocondensation (CC) of the carbanionic chelating ligand with the Cp* ligand (Scheme 1 ).…”
mentioning
confidence: 99%
“…Previous studies suggested that the oxidation of the Co(III) complex I to a Co(IV) [ I ] + is required to trigger the RE. 9a To clarify whether or not this oxidation is mandatory, the RE activation energies at the Co(III) and Co(IV) states were compared. Note that, whereas the Co(IV) transition states were readily located by using a simple linear transit procedure, the Co(III) ones required more-careful exploration of the potential-energy surface.…”
mentioning
confidence: 99%